Genome-wide linkage mapping of root system architecture-related traits in common wheat (Triticum aestivum L.) - Jin, Yirong; Wang, Yamei; Liu, Jindong; Wang, Fuyan; Qiu, Xiaodong; Liu, Peng (Frontiers in Plant Science, 2023)
Identifying loci for root system architecture (RSA) traits and developing available markers are crucial for wheat breeding. In this study, RSA related traits, including total root length (TRL), total root area (TRA) and number of root tips (NRT), were evaluated in the Doumai/Shi4185 recombinant inbred lines (RIL) population under hydroponics. In addition, both the RILs and parents were genotyped using the wheat 90K single-nucleotide polymorphism (SNP) array. In total, two quantitative trait loci (QTLs) each for TRL (QTRL.caas-4A.1 and QTRL.caas-4A.2), TRA (QTRA.caas-4A and QTRA.caas-4D), and NRT (QNRT.caas-5B and QNRT.caas-5D) were identified and each explaining 5.94-9.47%, 6.85-7.10% and 5.91-10.16% phenotypic variances, respectively. Among these, QTRL.caas-4A.1 and QTRA.caas-4A overlapped with previous reports, while QTRL.caas-4A.2, QTRA.caas-4D, QNRT.caas-5B, and QNRT.caas-5D were novel. The favorable alleles of QTRL.caas-4A.1, QTRA.caas-4A, and QTRA.caas-5B were contributed by Doumai, whereas the favorable alleles of QTRL.caas-4A.2, QTRA.caas-4D, and QTRA.caas-5D originated from Shi 4185. Additionally, two kompetitive allele-specific PCR (KASP) markers, Kasp_4A_RL (QTRA.caas-4A) and Kasp_5D_RT (QNRT.caas-5D), were developed and validated in 165 wheat accessions. This study provides new loci and available KASP markers, accelerating wheat breeding for higher yields.